2020
DOI: 10.1093/ajcp/aqaa016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SF3B1/DNMT3A Comutations With DNMT3A or SF3B1 Mutation Alone in Myelodysplastic Syndrome and Clonal Cytopenia of Undetermined Significance

Abstract: Objectives To compare the clinical significance of SF3B1/DNMT3A Comutations with SF3B1 or DNMT3A mutation alone in myelodysplastic syndrome (MDS) and clonal cytopenia of undetermined significance (CCUS). Methods We identified and compared 31 patients with only DNMT3A mutation, 48 patients with only SF3B1 mutation, and 16 patients with only SF3B1/DNMT3A comutations. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…SF3B1 emerges to be the only gene for which somatic mutations are associated with a good prognosis in MDS [16]. Our results intently aligned with published reports [17,11] as our patients harbouring the frameshift mutations of SF3B1 showed improved clinical outcome with event-free survival. Furthermore, one patient with a distinct stop-gained frameshift mutation (Y634X) showed worse prognosis and succumbed to the disease during the follow-up period.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…SF3B1 emerges to be the only gene for which somatic mutations are associated with a good prognosis in MDS [16]. Our results intently aligned with published reports [17,11] as our patients harbouring the frameshift mutations of SF3B1 showed improved clinical outcome with event-free survival. Furthermore, one patient with a distinct stop-gained frameshift mutation (Y634X) showed worse prognosis and succumbed to the disease during the follow-up period.…”
Section: Discussionsupporting
confidence: 89%
“…A study by Martin et al [10] showed worse overall survival (OS) with increased tendency for disease progression in patients who carried double mutation of DNMT3A and SF3B1. However, Song et al [11] ascertained that DNMT3A/SF3B1 double mutation showed a better prognosis than patients with DNMT3A single mutation. However, data on the impact of DNMT3A/ASXL1 and DNMT3A/TET2 co-mutation on the patients' prognosis in MDS is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in SF3B1 have been implicated as common drivers of hematologic malignancies. Somatic SF3B1 mutations are found in approximately 30% of patients with MDS and as many as 80% of patients with the MDS subtype characterized by ring sideroblasts (MDS-RARS) [ 41 , 56 , 57 ] . These mutations are also present in 20% of patients with myelodysplastic/myeloproliferative neoplasm (MDS/MPN) [ 41 ] and in 15% of patients with chronic myeloid leukemia (CLL) [ 58 60 ] .…”
Section: Sf3b1 Mutations In Cancermentioning
confidence: 99%
“…These mutations, together with those of SRSF2 and SF3B1, account for about 70% of cases. [12][13][14] In general, CCUS and other premalignant cytopenias differ from MDS by the lack of myelodysplastic features or increased blasts. Acquisition of additional mutations and dysplasia 15 may eventually lead to MDS (Figure 1).…”
Section: Premalignant Clonal Cytopenias and Myelodysplastic Syndromes...mentioning
confidence: 99%